2012
DOI: 10.1080/19768354.2011.611256
|View full text |Cite
|
Sign up to set email alerts
|

Perphenazine and trifluoperazine induce mitochondria-mediated cell death in SH-SY5Y cells

Abstract: Drug-induced parkinsonism has been associated with an increased risk for Parkinson's disease. Antipsychotic drugs have long been known to cause parkinsonian symptoms. However, it remains unclear whether antipsychotics can directly damage the nigrostriatal pathway. In the present study, we investigated the toxicity mechanism of two typical antipsychotics, perphenazine and trifluoperazine, in a human dopaminergic cell line, SH-SY5Y. Perphenazine and trifluoperazine induced mitochondrial damage as evidenced by fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…2 . These results are consistent with those reported for TFP in other diseases and tissue types ( 19 , 21 , 26 ). The present study showed that TFP upregulated the ratio of Bax/Bcl-2 to promote MC apoptosis in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…2 . These results are consistent with those reported for TFP in other diseases and tissue types ( 19 , 21 , 26 ). The present study showed that TFP upregulated the ratio of Bax/Bcl-2 to promote MC apoptosis in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…Hong et al (2012) suggest that highly plausible autophagy follows the mitochondrial fragmentation because the authors observed massive mitochondrial fragmentation at a very early phase of the perphenazine (25 μM) and trifluoperazine (25 μM) treatment in SH‐SY5Y neuroblastoma (Hong et al, 2012). It is worth noting that mitochondrial dysregulation and fragmentation resulting in autophagic clearance have been frequently observed in neurodegenerative diseases (Cho et al, 2010).…”
Section: The Impact Of Phenothiazine Derivatives On Autophagymentioning
confidence: 99%
“…induction: ↑LC3II/LC3I ratio (Zhang et al, 2007); LC3‐II (Höllerhage et al, 2014); autophagosome generation stimulation (Höllerhage et al, 2014); massive mitochondrial fragmentation (Hong et al, 2012); cell number per field, LC3‐GFP spot number per cell, LC3‐GFP spot area per cell, and LC3‐GFP spot intensity, mTOR‐independent pathway (Zhang et al, 2007);…”
Section: The Impact Of Phenothiazine Derivatives On Autophagymentioning
confidence: 99%
“…Perphenazine is an antipsychotic drug, a phenothiazine derivative, used to treat schizophrenia and bipolar disorders [ 9 , 10 ]. It acts on all the levels of the central nervous system, particularly the hypothalamus [ 11 , 12 ]. Research has suggested that phenothiazines, including perphenazine, possess anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…When the membrane is exposed to ions, such as protons and hydroxide ions, electrostatic interactions can be altered. Biologically active molecules, including phospholipids and drugs, possess acidic or basic groups, modulating their structure and interactions [ 12 ]. Drugs are either weak bases or weak acids, and either is uncharged or charged in physiological pH.…”
Section: Introductionmentioning
confidence: 99%